Point-of-Care Troponin T Testing in the Management of Patients with Chest Pain in the Swedish Primary Care. (10th January 2013) - Nilsson, Staffan; Andersson, Per O.; Borgquist, Lars; Grodzinsky, Ewa; Janzon, Magnus; Kvick, Magnus; Landberg, Eva; Nilsson, Håkan; Karlsson, Jan-Erik
Abstract : Objective . To investigate the diagnostic accuracy and clinical benefit of point-of-care Troponin T testing (POCT-TnT) in the management of patients with chest pain. Design . Observational, prospective, cross-sectional study with followup. Setting . Three primary health care (PHC) centres using POCT-TnT and four PHC centres not using POCT-TnT in the southeast of Sweden. Patients . All patients ≥35 years old, contacting one of the primary health care centres for chest pain, dyspnoea on exertion, unexplained weakness, and/or fatigue with no other probable cause than cardiac, were included. Symptoms should have commenced or worsened during the last seven days. Main Outcome Measures . Emergency referrals, patients with acute myocardial infarctions (AMI), or unstable angina (UA) within 30 days of study enrolment. Results . 25% of the patients from PHC centres with POCT-TnT and 43% from PHC centres without POCT-TnT were emergently referred by the GP (P = 0.011 ). Seven patients (5.5%) from PHC centres with POCT-TnT and six (8.8%) from PHC centres without POCT-TnT were diagnosed as AMI or UA (P = 0.369 ). Two patients with AMI or UA from PHC centres with POCT-TnT were judged as missed cases in primary health care. Conclusion . The use of POCT-TnT may reduce emergency referrals but probably at the cost of an increased risk to miss patients with AMI or UA.